Environmental enrichment attenuates social isolation-exacerbated postoperative cognitive dysfunction in aged mice via inhibition of RAGE-HMGB1 proinflammatory signaling - Sha Li; Hongyan Wang; Mingzhe Qin; Wei Huang; Huifang Gao; Xiaoyang Song; Xiaolong Chen; Bixi Li (Brain Research Bulletin, 2025)
Microglial overactivation, leading to neuroinflammation, plays a pivotal role in the development of postoperative cognitive dysfunction (POCD). However, the reasons behind varying inflammatory and cognitive reactions to similar surgical stresses among individuals remain enigmatic. Social isolation (SI), a prevalent psychosocial stressor among older adults, is known to intensify neuroinflammatory reactions and may represent a crucial but overlooked risk factor for POCD. Utilizing aged mouse models, our study reveals that four weeks of preoperative SI considerably worsens surgical-related cognitive deficits, specifically affecting spatial memory (evident from increased Barnes maze latency) and recognition memory (manifested by decreased novel object preference). From a mechanistic perspective, SI predominantly boosts HMGB1-RAGE signaling (rather than TLR4), leading to M1 microglial activation (marked by elevated iNOS and CD86 levels), synaptic destabilization (indicated by decreased PSD95 and SYN), and elevated proinflammatory cytokines. Genetic downregulation of RAGE reverses these alterations, whereas environmental enrichment (EE) offers neuroprotective effects by specifically blocking the RAGE–HMGB1 pathway. Notably, RAGE overexpression negates the beneficial effects of EE, emphasizing the key role of this receptor in SI-induced susceptibility to POCD. Our findings experimentally demonstrate that SI predisposes individuals to POCD via RAGE-dependent neuroinflammatory priming and suggest EE as a potential targeted intervention. These results could inform tailored preventative measures for elderly surgical patients at risk.